Overhead photoselective shade films mitigate effects of climate change by arresting flavonoid and aroma composition degradation in wine - Marigliano, Lauren E.; Yu, Runze; Torres, Nazareth; Medina-Plaza, Cristina; Oberholster, Anita; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2023)
Overhead photoselective shade films installed in vineyards improve berry composition in hot grape-growing regions. The aim of the study was to evaluate the flavonoid and aroma profiles and composition of wines from Cabernet Sauvignon grapes (Vitis vinifera L.) treated with partial solar radiation exclusion. Grape must from overhead shade film treatments that permitted different amounts of ultraviolet and near infra-red solar radiation spectra (D1, D3, D4, D5) and an uncovered control (C0) were vinified in triplicates. The wines from D4 treatment had greater color intensity and total phenolic index due to co-pigmentation with anthocyanins. Shade film wines D5 and D1 from the 2020 vintage demonstrated increased total anthocyanins in the hotter of the two experimental years. In 2021, reduced cluster temperatures optimized total anthocyanins in D4 wines. Reduced cluster temperatures modulated anthocyanin acylation, methylation and hydroxylation in shade film wines. Volatile aroma composition was analyzed using gas chromatography mass spectroscopy (GCMS) and D4 wines exhibited a more fruity and pleasant aroma profile than C0 wines. Results provided evidence that partial solar radiation exclusion in the vineyard using overhead shade films directly improved flavonoid and aroma profiles of resultant wines under hot vintage conditions, providing a tool for combatting air temperatures and warmer growing conditions associated with climate change.